2013
DOI: 10.1063/1.4821140
|View full text |Cite
|
Sign up to set email alerts
|

Controlled synthesis of SnO2 nanostructures with different morphologies and the influence on photocatalysis properties

Abstract: SnO2 nanoparticles, nanoflowers, and nanorods of highly crystalline were synthesized via a simple hydrothermal method. The size and morphology of the SnO2 nanostructures could be controlled by varying the NaOH concentration of the precursor solutions. The SnO2 structures appeared to be sphere-like nanoparticles with diameters in the range of 5–10 nm in lower NaOH concentrations. In higher NaOH concentrations, the nanostructures showed orientation growth behavior and were flower-like or rod-like in morphology. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…13,15,[23][24][25] ZnO and SnO 2 are important n-type semiconductors (E gap ¼ 3.37 eV and 3.6 eV, respectively at 300 K) that have attracted considerable interest in diverse applications. 3,[26][27][28][29] The literature has reported that the junction of these semiconductors, forming a suitable type-II heterostructure, can further enhance their properties mainly due to the efficient charge separation. 13,23,25,30 Recently, Park and co-workers synthesized SnO 2 -core/ZnOshell nanowires through a two-step process consisting of a thermal evaporation followed by an atomic layer deposition.…”
Section: Introductionmentioning
confidence: 99%
“…13,15,[23][24][25] ZnO and SnO 2 are important n-type semiconductors (E gap ¼ 3.37 eV and 3.6 eV, respectively at 300 K) that have attracted considerable interest in diverse applications. 3,[26][27][28][29] The literature has reported that the junction of these semiconductors, forming a suitable type-II heterostructure, can further enhance their properties mainly due to the efficient charge separation. 13,23,25,30 Recently, Park and co-workers synthesized SnO 2 -core/ZnOshell nanowires through a two-step process consisting of a thermal evaporation followed by an atomic layer deposition.…”
Section: Introductionmentioning
confidence: 99%
“…It shouldb en oted that in other reports of SnO 2 synthesized at alkaline conditions ar ich variety of morphologies are observed, including nanoflowers, nanorods, and nanospheres. [44][45][46] The powder X-ray diffraction (PXRD) peak asymmetry towards lower angles indicates al arger unit cell size for parts of the diffractingv olume. This may be attributed to surface relaxation from hydroxylationo ri nclusion of OH defects.…”
Section: Resultsmentioning
confidence: 99%
“…The result shows that the SnO 2 /Carbon/PANI composite displayed a high photocatalytic activity. The enhanced photocatalytic efficiency of SnO 2 /Carbon/PANI was 35 SnO 2 (20 mg) MO (50 ml, 20 mg l −1 ) UV 500 W Mercury Lamp 25 min ≈95% Qizhao Wang et al 50 PANI/BiOCl (50 mg) MO (50 ml, 10 mg l −1 ) Visible Light 500 W Xenon Lamp 210 min 67% Hong-Ryun Jung et al 51 Co 0.5 Mn 0.5 Fe 2 O 4 -PANI (20 mg) MO (100 mL,20 mg l −1 ) Visible Light 120 min 92% Jianguo Zhang et al 52 Ag 3 PO 4 -PANI-GO (60 mg) MO (30 ml, 12 mg l −1 ) Visible Light 350 W Xenon Lamp 25 min 98% Yanjun Chen et al 53 PANI/Ag 3 PO 4 /NiFe 2 O 4 (25 mg) MO (50 ml, 10 mg l −1 ) Visible Light 65 W Visible Lamp 25 min 95% Mouheb Sboui et al 54 TiO 2 -PANI/Cork (100 mg) MO (100 ml, 15 mg l −1 ) Nature Light 210 min 95.20% Shreya Saha et al 55 PANI (50 mg) MO (50 ml, 10 mg l −1 ) UV 100 W Mercury Lamp 120 min 97.95% likely attributed to synergistic effect and most efficient separation and transfer of photogenerated electrons and holes. Also, this work indicated that SnO 2 /Carbon/PANI nanocomposites could be applied in the organic pollutants removal by the photocatalytic reaction.…”
Section: Discussionmentioning
confidence: 99%
“…They believe that the synergistic effect between PANI and BiOCl improves the photocatalytic performance of PANI/BiOCl nanocomposites. 35 In previous studies, the SnO 2 /Carbon composites synthesized as electrode materials have the advantages of small particle size, high dispersion, excellent electrochemical performance and simple synthesized method. 36 Therefore, we used SnO 2 /Carbon as the matrix to synthesize SnO 2 /Carbon/PANI core-shell structure composites by a simple liquid phase method, and deeply investigated its structure and photocatalytic activity.…”
mentioning
confidence: 99%